Public health and swine production medicine aspects of vH1N1 influenza virus - Reece, Thomas Ray (Kansas State University, 2012)
Variant H1N1 influenza (vH1N1) virus is an issue both in swine production medicine and in the arena of public health. Influenza viruses can infect but not always produce disease in avian, humans and swine. Swine are unique among the three previously mentioned species in that their respiratory epithelium possesses three receptor sites for the virus types common to each of the three mentioned species. Swine influenza virus (SI) is common and widespread in nearly all Midwestern swine herds and can be transmitted by both direct contact and aerosolization. All of the three previously mentioned species have the potential to re-assort (produce virons containing genetic material of different virons to produce a unique influenza virus (IV). Because of their three specific receptor sites, swine have the greatest re-assortment capability. This re-assortment has the potential is a low mortality/high morbidity disease that is a substantial cost to the swine industry due to its negative effect on production parameters such as average daily gain (ADG) and feed efficiency (FE). It is a public health concern due to its potential to produce different virus types which may have increased mortality/morbidity in humans. Avian are the IV reservoir and have the ability to introduce virus types that are foreign to specific populations in all venues on the planet. It is in the mutual best interest of public health and swine production to mitigate the introduction of different virus types in swine and to control existing infections in swine populations with a goal of establishing SI-free herds. Mitigation for swine populations can occur through vaccination, diagnosis/isolation, and Biosecurity procedures designed to reduce/eliminate IV introduction into swine production facilities. In addition, preventing the interaction of infected humans with swine is another component of swine population Biosecurity.
Keywords: vH1N1; Public Health (0573)